PROBLEM BASED LEARNING MENGGUNAKAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS KELAS IV B SD ISLAM AL MADINA SEMARANG - Fitri Mulia; Veryliana Purnamasari; Sukamto (STKIP Subang, 2023)
This study aims to determine the PBL (Problem-Based Learning) learning model using audio-visual media to improve student learning outcomes in class IV B Science Science at SD Islam Al Madina, Semarang. This study used a pre-experimental type of research, namely one group pretest-posttest design using saturated sampling techniques and the instruments used in this study were instruments in the form of pretest and posttest questions. The population of this study was all students in class IV B at Al Madina Islamic Elementary School, Semarang. The data used are interview observations and tests. The results showed that the pretest average score was 48.57 and the posttest average score was 82.85, meaning that the learning outcomes of students had increased, the average gain test was 67.38 which was classified as a fairly effective criterion, and the results of the paired sample test shows 0.000 <0.05 then H0 is rejected and Ha is accepted. So it was concluded that problem-based learning using audio-visual media can improve student learning outcomes in class IV B Islamic Al Madina Islamic Elementary School Semarang City.